RbSn2(PO4)3, a NASICON-type phosphate - Dan Zhao (Acta Crystallographica Section E, 2011)
The title compound, rubidium ditin(IV) tris(phosphate), RbSn2(PO4)3, belongs to the NASICON-type family of phosphates and crystallizes in the space group Roverline{3}. The structure is composed of PO4 tetrahedra (1 symmetry) and two slightly distorted SnO6 octahedra, both with 3. symmetry, which are interlinked through corner-sharing O atoms to form a 3∞[Sn2(PO4)3]− framework. The Rb+ cations are located on threefold inversion axes in the voids of this framework and exhibit a coordination number of 12. The crystal studied was twinned by merohedry with a component ratio of 0.503:0.497.